La misura della qualità di vita e dell’utilità in farmacoeconomia: strumenti e loro applicazioni in una rassegna di letteratura - Chan, Ya-Ting (Farmeconomia. Health economics and therapeutic pathways, 2002)
In a climate of economic scarcity, decisions about the allocation of healthcare resources need to be made explicit. An economic evaluation is able to identify and quantify the relationship between an input of resources and an output, hence to appreciate the efficiency of the project. One of the recent methodological approaches that has been used increasingly in health economic evaluations is the ‘cost-utility analysis’ (CUA). CUA considers benefits in utility terms and uses a unique index to assess them. We investigated the generic measurements of health related quality of life in the economic evaluation. Different instruments for evaluating quality of life and utility were categorized and briefly introduced. Literatures published in the journal “PharmacoEconomics” in 1997-2001 regarding quality of life and utility were reviewed. We were especially interested in the application of health profile SF-36 and utility measure EQ-5D. Selected articles were further analyzed and some issues concerning the methodologies of quality of life and utility are discussed.